A Metabonomic Approach to Analyze the Dexamethasone-Induced Cleft Palate in Mice - Zhou, Jinglin (Hindawi Publishing Corporation, 2011)
Mice models are an important way to understand the relation between the fetus with cleft palate and changes of maternal biofluid. This paper aims to develop a metabonomics approach to analyze dexamethasone-induced cleft palate in pregnant C57BL/6J mice and to study the relationship between the change of endogenous small molecular metabolites in maternal plasma and the incidence of cleft palate. To do so, pregnant mice were randomly divided into two groups. The one group was injected with dexamethasone. On E17.5th day, the incident rates of cleft palate from embryos in two groups were calculated. The (1)H-NMR spectra from the metabolites in plasma in two groups was collected at same time. Then the data were analyzed using metabonomics methods (PCA and SIMCA). The results showed that the data from the two groups displayed distinctive characters, and the incidence of cleft palate were significantly different (P < .005). To conclude, this study demonstrates that the metabonomics approach is a powerful and effective method in detecting the abnormal metabolites from mother in the earlier period of embryos, and supports the idea that a change from dexamethasone induced in maternal metabolites plays an important role in the incidence of cleft palate.